Possible role of gut microbes and host’s immune response in gut–lung homeostasis - Rastogi, Sonakshi; Mohanty, Sneha; Sharma, Sapna; Tripathi, Prabhanshu (Frontiers in Immunology, 2022)
The vast diversity of microbial communities reside in various locations of the human body, and they are collectively named as the ‘Human Microbiota.’ The majority of those microbes are found in the gastrointestinal and respiratory tracts. The microorganisms present in the gastrointestinal and the respiratory tracts are called the gut microbiota and the airway microbiota, respectively. These microbial communities are known to affect both the metabolic functions and the immune responses of the host. Among multiple factors determining the composition of gut microbiota, diet has played a pivotal role. The gut microbes possess enzymatic machinery for assimilating dietary fibers and releasing different metabolites, primarily short-chain fatty acids (SCFAs). The SCFAs modulate the immune responses of not only the gut but other distal mucosal sites as well, such as the lungs. Dysbiosis in normal gut flora is one of the factors involved in the development of asthma and other respiratory disorders. Of note, several human and murine studies have indicated significant cross-talk between gut microbiota and lung immunity, known as the gut–lung axis. Here, in this review, we summarize the recent state of the field concerning the effect of dietary metabolites, particularly SCFAs, on the “gut–lung axis” as well as discuss its impact on lung health. Moreover, we have highlighted the role of the “gut–lung axis” in SARS-CoV-2 mediated inflammation. Also, to analyze the global research progress on the gut–lung axis and to identify the knowledge gap in this field, we have also utilized the bibliographic tools Dimension database and VOS viewer analysis software. Through network mapping and visualization analysis, we can predict the present research trend and the possibility to explore new directions.